Pengaruh Harga dan Kualitas Pelayanan terhadap Kepuasan Pelanggan Starbucks Reserve Dewata - Dhyasa, Kadek Intan Dwi Cahyani; Heryanda, Komang Krisna (Universitas Pendidikan Ganesha, 2023)
Customer satisfaction is a customer response in the form of a feeling of satisfaction after comparing the product or service that is in mind to the expected product or service and the fulfillment of needs. Price and service quality are factors that influence customer satisfaction and have an important role in building customer satisfaction. This test aims to determine and prove the effect of price and service quality both collectively and individually on Starbucks Reserve Dewata customer satisfaction. The research design used is causal quantitative. The research subjects in this study were Starbucks Reserve Dewata customers who visited and bought products at Starbucks Reserve Dewata. The object of research in this study is price, service quality and customer satisfaction. The sample technique used in this study was purposive sampling technique. The sample in this study amounted to 130 respondents with the criteria of respondents taken, namely customers who visited and bought products at Starbucks Reserve Dewata more than twice in the last year. Data were collected by questionnaire and analyzed by multiple linear regression analysis. The results of this study are: (1) price and service quality have a significant effect on customer satisfaction Starbucks Reserve Dewata, (2) price has a positive and significant effect on customer satisfaction Starbucks Reserve Dewata (3) service quality has a positive and significant effect on customer satisfaction Starbucks Reserve Dewata.